Breast Cancer Metastasis in a Renal Carcinoma Pulmonary Metastasis: A Rare Example of Tumor-to-Tumor Metastasis - Áurea Lima; Isa Peixoto; Susana Sarandão; Daniel Melo; Ângelo Rodrigues; Helena Pereira (Case Reports in Oncological Medicine)
The tumor-to-tumor metastasis phenomenon remains fairly uncommon, with fewer than 100 cases described to present time. Virtually any tumor can be a donor or a recipient neoplasm. Nevertheless, renal carcinomas have been implicated as the most common malignant tumors to harbor metastasis, while lung and breast tumors are the most frequent donors. This article reports an extremely rare case of a breast cancer metastasis in a lung metastasis of clear cell type renal cell carcinoma that met all Campbell and coworkers’ tumor-to-tumor metastasis criteria. Additionally, we present the literature case reports of breast cancer metastasis in renal cell carcinomas and try to discuss the mechanisms underlying its occurrence. Since this phenomenon identification will impact the therapeutic strategy and it is not easily detected by image, the anatomopathological study of any and all suspicious lesions is of crucial importance. To the best of our knowledge, this is the first report of a metastasis inside a metastasis.